2019
DOI: 10.3892/ijo.2019.4801
|View full text |Cite
|
Sign up to set email alerts
|

PF‑114, a novel selective inhibitor of BCR‑ABL tyrosine kinase, is a potent inducer of apoptosis in chronic myelogenous leukemia cells

Abstract: A t(9;22) chromosomal translocation which forms the chimeric tyrosine kinase breakpoint cluster region (BCR)-Abelson murine leukemia viral oncogene homolog 1 (ABL) is a key mechanism underlying the pathogenesis of chronic myelogenous leukemia (CML). Pharmacological inhibition of BCR-ABL with imatinib (Gleevec) has been reported as an effective targeted therapy; however, mutations (including the kinase domain of ABL) suppress the efficacy of inhibitors. PF-114, a derivative of the third generation BCR-ABL inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Next, activation of caspase 3 was determined by neither by immunoblotting ( Figure 3 G) nor immunostaining ( Figure S2 ). No proteolytic processing of poly(ADPribose)polymerase (PARP) was observed upon cell exposure to CuO + NAC, whereas the reference compounds Dox or PF-114, a Bcr-Abl inhibitor [ 28 ], induced cleavage of PARP and caspase 3 in K562 cells ( Figure 3 G and Figure S2 ). Altogether, we interpreted the complex mode of cell death by CuO + NAC as a caspase-independent apoptosis coupled with an early necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Next, activation of caspase 3 was determined by neither by immunoblotting ( Figure 3 G) nor immunostaining ( Figure S2 ). No proteolytic processing of poly(ADPribose)polymerase (PARP) was observed upon cell exposure to CuO + NAC, whereas the reference compounds Dox or PF-114, a Bcr-Abl inhibitor [ 28 ], induced cleavage of PARP and caspase 3 in K562 cells ( Figure 3 G and Figure S2 ). Altogether, we interpreted the complex mode of cell death by CuO + NAC as a caspase-independent apoptosis coupled with an early necrosis.…”
Section: Resultsmentioning
confidence: 99%
“…Other new molecules are already under clinical trials e.g., PF-114, HQP1351 (Olverembatinib), and K0706 (Vodobatinib), which function competitively as inhibitors of BCR-ABL1 TK at the ATP-binding site ( Table 2 ) [ 249 ]. These inhibitors have presented an increased potency against a wide range of BCR-ABL1 mutations [ 249 , 250 , 251 , 252 ] and may overcome some the limitations of approved TKIs. Unlike other TKIs, Olverembatinib is able to bind to the kinase in the presence of T315I mutations since it does not form the hydrogen bond with the hydroxyl group at this residue [ 251 ].…”
Section: Therapeutic Approaches Against Resistancementioning
confidence: 99%
“…Here, we have demonstrated that the characteristic oncogene CRKL is the downstream effector of Hh‐GLI2 pathway, providing CRKL as a putative drug target for Hh‐related NSCLC. As a matter of fact, CRKL inhibitor PF‐114 has recently reported to induce tumour cell apoptosis 24 . Given that our studies only uncover CRKL is a critical transcriptional target of Hh‐GLI2 pathway in NSCLC cells, it will be interesting to test whether this transcriptional regulation also exists in other types of cancer.…”
Section: Discussionmentioning
confidence: 80%